2006
DOI: 10.1002/ejic.200600621
|View full text |Cite
|
Sign up to set email alerts
|

Size‐ and Shape‐Controlled Synthesis and Assembly of a Silver Nanocomplex in UV‐Irradiated TSA Solution

Abstract: In this paper we describe the size-controlled synthesis of a silver nanocomplex based on the reduction of silver nitrate (AgNO 3 ) by UV-irradiated tungstosilicate acid [H 4 (SiW 12 O 40 ), TSA] solution. This method allows the synthesis of ellipsoidal particles with an average size that is tunable between 2.4 and 84 nm by varying the molar ratio of silver nitrate to TSA, the pH of the reaction solution, and the reaction temperature. Silver nanorods can be formed from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The fact in which smaller Au NPs are formed with increasing the initial amount of Preyssler implies that the nucleation process is enhanced more than the growth of these nanoparticles. In this range, our findings verify the results of other studies such as Troupis et al [7,8,16] and Yang et al [28] in which POM served as both reducing agents and stabilizers in the synthesis of metal nanoparticles. They have reported that increasing the POM amount leads to formation of smaller nanoparticles.…”
Section: Effect Of Initial Preyssler Acid Concentrationsupporting
confidence: 95%
“…The fact in which smaller Au NPs are formed with increasing the initial amount of Preyssler implies that the nucleation process is enhanced more than the growth of these nanoparticles. In this range, our findings verify the results of other studies such as Troupis et al [7,8,16] and Yang et al [28] in which POM served as both reducing agents and stabilizers in the synthesis of metal nanoparticles. They have reported that increasing the POM amount leads to formation of smaller nanoparticles.…”
Section: Effect Of Initial Preyssler Acid Concentrationsupporting
confidence: 95%
“…This behaviour is similar to that found in many chemical reduction approaches to nanosystems because the nucleation and growth sequences are affected both by the relative concentrations of the reducing agent and the precursor. [24] The dependence of the products on the pH of the solution was also studied. The FESEM images show the prepared white products corresponding to pH values of 3.62 (a) and 4.45 (b) (as shown in Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[17] Sastry and coworkers used PW 12 O 40 3-ions to make phase-pure core-shell nanoparticles [18,19] and they also used PW 12 O 40 3-as a template for the in situ growth of metal nanoparticles, [20,21] star-shaped calcium carbonate crystals [22] and CdS nanoparticles. [23] Yang and coworkers prepared the 3D packed trigonal selenium microspheres by a hydrothermal process [24] and, recently, we have synthesised a tungstosilicate acid (TSA)-Ag nanocomplex based on the reduction of silver nitrate by a UV-irradiated tungstosilicate acid solution. [25] The size of the nanocomplex was in the range of 20-60 nm, with a mean diameter of 45 nm.…”
Section: Introductionmentioning
confidence: 99%
“…As the TSA template may be removed by simple dissolution in an alkaline medium, TSA can act as a suitable soft template to prepare nanomaterials. Our group has studied the size-controlled and shape-controlled synthesis of silver nanoparticles by the templates of TSA colloidal particles for the first time [30].…”
Section: Introductionmentioning
confidence: 99%